Democracy, communication and language in Europe's transnational political space - Peter A. Kraus (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2005)
The external communication of the European Union (EU) suffers from the fact that the flow of information from the Europe of institutions to the Europe of citizens has until now had little success in inspiring popular political participation. This problem can be related to the politics of language in the EU. The paper begins with a discussion of two prominent views of the European problematic of language and the public sphere. The essential interconnections between public political communication and the issue of language in the EU are set forth in contrast with these positions. The paper then turns to the main parameters of an EU language policy directed to the external sphere of communication. A possible strategy for shaping the relation between multilingualism and a transnational public sphere in Europe is sketched out in the final sections. – – Die Europäische Union (EU) hat im Bereich der öffentlichen Darstellung ihrer Politik Defizite: Bisher hat der Informationsfluss vom Europa der Institutionen zum Europa der Bürger nicht nennenswert dazu beigetragen, politische Partizipation im transnationalen Maßstab anzuregen. Das Problem verweist auf die Herausforderungen europäischer Sprachpolitik. Der Beitrag beginnt mit einer Diskussion von zwei prominenten Sichtweisen des Verhältnisses von Sprache und Öffentlichkeit in Europa. Wesentliche Verbindungen zwischen Sprachenfrage und den Strukturen öffentlicher Kommunikation in der EU werden im Kontrast zu diesen Positionen herausgearbeitet. Im Anschluss daran werden die Hauptparameter der auf die Sphäre der externen Kommunikation gerichteten Sprachpolitik der EU kritisch betrachtet. Der Schlussteil des Beitrags skizziert eine mögliche Strategie zum Umgang mit der Sprachenvielfalt in einer transnationalen europäischen Öffentlichkeit.
Keywords: 300